Challenging Misconceptions about Islam through Islamic English: An Assertive Speech Act Approach in Interfaith Dialogue - Zulfah, Siti; Triyoko, Hanung (Journal of Language and Literature Studies, 2025)
Research has shown that interfaith dialogue is essential for fostering mutual understanding and peace among different religious communities, yet misconceptions and stereotypes, particularly about Islam, continue to hinder productive communication. The role of language, especially Islamic English, in bridging these gaps and facilitating accurate representations of Islam remains underexplored in the context of interfaith dialogue. This study investigates the role of Islamic English in addressing these misconceptions by analyzing its use through the framework of assertive speech acts. Adopting a mixed-methods approach, the study examines a publicly available YouTube video of an interfaith dialogue conference titled "Islam, Judaism, and Christianity – A Conversation", hosted by SMAADallas. A total of 135 occurrences of Islamic English terms were identified and analyzed based on their frequency, meanings, and pragmatic functions. The qualitative phase applies assertive speech act analysis to explore how these terms reinforce Islamic identity, clarify religious concepts, and establish common ground with other faiths. The findings reveal that the Muslim speaker strategically employs Islamic English through assertive acts such as asserting, stating, denying, describing, and explaining to challenge stereotypes, correct misunderstandings, and assert Islamic theological and historical truths. The study highlights how Islamic English serves as a discursive strategy in interfaith communication, ensuring linguistic and theological accuracy while fostering mutual respect. Ultimately Islamic educators and interfaith dialogue practitioners can incorporate Islamic English strategically to clarify Islamic identity, correct misconceptions, engage diverse audiences, and promote mutual respect and peaceful coexistence in educational and interfaith settings.